1998
DOI: 10.1038/sj.bjp.0702230
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5‐HT6 receptors in nigro‐striatal function in rodents

Abstract: 1 4-Amino-N-(2,4 bis-methylamino-pyrimidin-4-yl) benzene sulphonamide (Ro 04-6790) is a potent, selective and competitive antagonist for the 5-HT 6 receptor which can be detected in the cerebro-spinal uid (CSF) of rats following intraperitoneal administration. Since 5-HT 6 receptor mRNA and 5-HT 6 receptor-like immunoreactivity have been shown to be present in the striatum, the purpose of the present study was to evaluate the e ect of 5-HT 6 receptor antagonism on haloperidol-and SCH 23390-induced catalepsy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 14 publications
4
35
0
1
Order By: Relevance
“…Compelling evidence suggests that 5-HT modulates cholinergic signalling in several brain areas (Cassel and Jeltsch, 1995;Bourson et al, 1998). Depending upon the specific region involved, this functional interaction may powerfully influence cognitive functions as well as motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests that 5-HT modulates cholinergic signalling in several brain areas (Cassel and Jeltsch, 1995;Bourson et al, 1998). Depending upon the specific region involved, this functional interaction may powerfully influence cognitive functions as well as motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this speculation, behavioral studies suggest that 5-HT 6 receptors mediate a circumscribed behavioral pattern that requires an intact (Values are expressed as mean optical density for CA2 and CA3 Ϯ SEM for 10 animals.) cholinergic system (Bourson et al 1995;Bourson et al 1998). Furthermore, aniracetam has been shown to modulate cholinergic systems (Bartolini et al 1992;Pepeu and Spignoli 1989).…”
Section: Densensitization Modulatorsmentioning
confidence: 99%
“…97 Studies in rodents have suggested a role for 5-HT 6 receptors in the control of cholinergic neurotransmission, 98 and the selective 5-HT 6 receptor antagonist SB-271046 has been shown to improve memory retention in the water maze test of spatial learning and memory. 99 Thus, 5-HT 6 receptors may have an important future role in the treatment of cognitive deficits in neuropsychiatric illnesses such as Alzheimer's disease and schizophrenia.…”
Section: Serotonin 5-ht 4 Receptorsmentioning
confidence: 99%